An effective rabies treatment in exposed monkeys: a single dose of interferon inducer and vaccine - Baer, G. M. (1979)
Rhesus monkeys were injected with lethal doses of rabies virus and then treated with a variety of treatment combinations. The one found most successful was one dose of an interferon inducer (poly(I)—poly(C) complexed to poly-L-lysine and carboxymethyl-cellulose) and one dose of human diploid rabies vaccine. This combination proved to be as effective as hyperimmune serum and vaccine, and much better than vaccine alone. The combination of the interferon inducer plus vaccine could be administered at least up to 48 hours after the very severe challenge given and still provide marked protection.